PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DAN PICTURE AND PICTURE PADA MATERI SISTEM PERNAPASAN DI KELAS VIII SMP NEGERI 2 DOLOK PANRIBUAN - Sitompul, Wasteria; Huda, M. Komarul (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2021)
This study compares student learning outcomes using the Example-Non-Example and Picture and-Picture learning models on the Respiratory System in eighth-grade students at SMP Negeri 2 Dolok Panribuan. This study aims to determine whether there are differences in student learning outcomes when learning about the respiratory system using the Example-Non-Example and Picture-and-Picture models, and to determine the magnitude of the differences in student learning outcomes when learning about the respiratory system using the Example-Non-Example and Picture-and-Picture models. The population in this study was all eighth-grade students in the second semester of SMP Negeri 2 Dolok Panribuan in the 2019/2020 academic year, consisting of six classes with a total of 179 students. Sampling was conducted using cluster random sampling. The sample taken in this study was divided into two classes: class VIII-2 (experimental class I) using the Example-Non-Example learning model and class VIII-5 (experimental class II) using the Picture-and-Picture learning model. Data analysis was performed by calculating the average score and standard deviation, and hypotheses were tested using the t-statistic or t-test at a significance level of α = 0.05. Based on the research results obtained, the total pre-test and post-test scores for experimental class I were 1350 and 2670 while the average scores were 42.18 and 83.43. In experimental class II the total pre-test and post-test scores for experimental class II were 1470 and 2485 while the average scores were 45.93 and 77.65. When comparing the average post-test value of experimental class I (83.43) with experimental class II (77.65), a difference in student learning outcomes was obtained of 5.78 where the learning outcomes of experimental class I with the Example Non Example model were higher than the learning outcomes of experimental class II with the Picture and Picture learning model. The results of hypothesis testing using the